STUDI KOMPERATIF TENTANG HAK-HAK ANAK DITINJAU MENURUT HUKUM ISLAM DAN UNDANG-UNDANG TENTANG PERLINDUNGAN ANAK DI INDONESIA - Samsul Arifin (Progresif : Media Publikasi Ilmiah, 2022)
Children's rights are something very vital in a child's life. Fulfillment of children's rights is a part that parents must always pay attention to. Children's rights are often overlooked because of certain activities and interests. Children's rights in Positive Law are regulated in the Law. This article is actually a compilation of laws in Indonesia in treating children very well, in terms of the Law on Child Protection and Islamic Law. Child rights such as the right to life, the right to education, the right to health insurance, etc. have all been fulfilled. . However, there are several children's rights that have not been fully fulfilled because of the obstacles that make this right not fulfilled. Namely "children have the right to know their parents, be raised and cared for by their own parents". In the text in writing there is no thing that is considered contrary to Islam, however, in its implementation children often do not get their rights to know who the real parents are, this is due to the enactment of laws that substantially conflict with the enactment of the Law, as exemplified in the description regarding the making of a birth certificate and the process of adoption (child adoption)